LIKE & EDIT PAPUA: Literasi Keuangan & Edukasi Digital Terintegrasi Untuk Pelaku Usaha Mikro "Mama-Mama" Asli Papua - Patma, Kurniawan; Falah, Syaikhul; Seralurin, Yohanes Cores; Matani, Cornelia Desiana; Sesa, Pascalina V.S. (The Community Engagement Journal, 2025)
This community service project, titled LIKE & EDIT PAPUA, was implemented with the aim of enhancing financial and digital literacy among indigenous Papuan women micro entrepreneurs, commonly known as “Mama-Mama Papua.” The program was initiated based on field findings that highlighted a lack of financial bookkeeping practices, inadequate separation of business and household finances, and very low digital literacy levels among local micro-entrepreneurs. To address these issues, the program consisted of participatory training and mentoring activities across three target villages: Abar, Skow Yambe, and Waibron. The financial literacy component (LIKE PAPUA) focused on equipping participants with skills in basic bookkeeping, such as maintaining cash books, preparing income statements, and understanding production costs. Meanwhile, the digital education component (EDIT PAPUA) trained participants to use mobile applications and online platforms to digitally market their products through social media and marketplaces like Shopee and GoFood. The project successfully empowered 62 beneficiaries by providing them with the tools to manage their business finances independently and market their products online. The measurable impact included an increase in business income, improved access to formal financial services, and higher confidence among the women in managing their enterprises. The use of culturally contextualized, participatory methods proved effective in facilitating sustainable behavioral change. This initiative demonstrates that integrating financial literacy, digital skills, and local wisdom can foster inclusive economic empowerment and has strong potential for replication in other indigenous communities in Papua and beyond. Keywords: financial literacy, digital marketing, women empowerment, indigenous entrepreneurship, Papua